SISTEM PAKAR DIAGNOSA PENYAKIT GANGGUAN TIDUR DENGAN METODE FORWARD CHAINING BERBASIS WEB (STUDI KASUS : UPTD PUSKESMAS TELAGA DEWA KOTA BENGKULU) - Ahmad Revaldo; Yupianti Yupianti; Ila Yati Beti (Jurnal Media Infotama, 2023)
Abstract—The necessities of life force people to work to fulfill their daily lives. In general, humans work during the day and rest at night. A lot of time spent working requires humans to rest to recover their physical condition. Sleep is an important phase in daily activities that is useful for balancing human life. Everyone's sleep needs are different. Many people are long-sleepers who need 9 to 10 hours of sleep a night while others are short-sleepers who only need less than 6 hours of sleep each night. Long sleep is not always associated with sleep disturbances. Besides that most people are not medically trained, therefore the authors intend to design an "expert system for diagnosing sleep disorders using the web-based forward chaining method" which can be accessed via http://puskesmastelagadewa.com/. This application is expected to be used by the community in early diagnosis as a prevention of more severe disease. This system is designed using the PHP programming language and MySQL database, the resulting expert system is able to help patients diagnose sleep disorders while providing solutions to the disease. From the test results, it is obtained that 100% functionality runs according to system requirements. In the system testing carried out at the Telaga Dewa Health Center UPTD, Bengkulu City, symptoms and diseases were obtained from 7 existing sample data.